A Modified Human Development Index and Poverty in the Villages of West Seram Regency, Maluku Province, Indonesia - Amaluddin, Amaluddin; Payapo, Rukmuin W.; Laitupa, Abdul A.; Serang, Mohammad R. (International Journal of Economics and Financial Issues, 2018)
The first purpose of this paper is to develop or construct a new human development composite index and applied to measure the performance of human development in the villages of West Seram Regency, Maluku Province. The second, to develop the priority scale of human development for development planning. The third, analyzing the effect of HDI's indicators on poverty level. This paper applies PCA, clustering analysis and panel data regression. PCA method generates index which we called Modified Human Development Index (MHDI). Based on clustering analysis, the number of villages in the high cluster is 6 villages, the medium cluster is 13 villages and low cluster is 14 villages. The modified human development performance has an important role for poverty alleviation and improving the level of people's welfare in the villages. This paper also revealed empirical study that the HDI's indicators have negative relationships and significant effect on poverty rate. Keywords: Human Development, Poverty, PCA, Clustering, Panel Data, Villages JEL Classifications: C3, C4, O1, I3